Study of Cord Blood Erythropoietin, Leptin and Adiponectin Levels in Neonates with Hypoxic Ischemic Encephalopathy - Hagag, Adel A.; El Frargy, Mohamed S.; Abd El-Latif, Amal E. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Hypoxic ischemic encephalopathy (HIE) is a serious condition which results in neonatal morbidity and mortality. Early prediction of HIE especially in the first six hours of birth leads to early treatment with better prognosis. Aim: The aim of this study was to compare the concentrations of leptin, adiponectin, and erythropoietin between normal neonates and those with HIE for the possible use of these markers for assessment of the degree of HIE and as markers for early prediction of HIE. Patients and Methods: This study was carried out on 50 appropriate for gestational age (AGA) neonates with HIE born in Tanta University Hospital during the period from June 2016 to March 2018 (Group I). This study also included 50 appropriate for gestational age (AGA) normal neonates not suffering from any complications and matched with group I in age and sex as a control group (Group II). For all neonates in both groups, the following were done: Complete prenatal, natal, and postnatal history, assessment of APGAR score at 5 and 10 minutes, complete clinical examination with special account on clinical evidence of encephalopathy including hypotonia, abnormal oculomotor or pupillary movements, weak or absent suckling, apnea, hyperpnea, or seizures, measurement of cord blood gases and measurement of serum erythropoietin, leptin and adiponectin levels by ELISA immediately after birth. Results: There were no significant differences between Group I and Group II regarding gestational age, male to female ratio, mode of delivery, and weight while there were significant differences regarding Apgar score at 1 and 5 minutes with significantly lower Apgar score at 1 and 5 minutes in group I compared with Group II. There were significantly lower cord blood PH and adiponectin level and significantly higher cord blood Leptin and erythropoietin in group I compared with group II. There were significant differences between cord blood adiponectin, leptin, erythropoietin, and PH in different degrees of HIE with significantly lower cord blood adiponectin and PH and significantly higher cord blood leptin and erythropoietin in severe degree of hypoxia compared with moderate degree and in moderate degree compared with mild degree of hypoxia. There was a significant positive correlation between cord blood erythropoietin and leptin and a significant negative correlation between cord blood erythropoietin and both adiponectin and PH in studied neonates with hypoxia. ROC curve showed that EPO had the best sensitivity and specificity followed by leptin then adiponectin while the PH had the least sensitivity and specificity as early predictors of hypoxic neonates. Conclusion and Recommendations: Neonates with HIE had lower cord blood PH and adiponectin levels and higher leptin and erythropoietin levels than normal healthy neonates at birth and during the early postnatal period. The significant differences between cord blood erythropoietin, leptin, and adiponectin between neonates with hypoxia compared with normal neonates may arouse our attention about the use of these markers in the cord blood as early predictors of neonatal HIE which can lead early treatment and subsequently better prognosis.
Keywords: Hypoxic ischemic encephalopathy